ReFocus: The Films of Wallace Fox - Fisher, Andrew H.; Floyd, Jacob; Hearne, Joanna; Hogan, David J.; Leeder, Murray; Rhodes, Gary D.; Rhodes, Gary D.; Rutkowski, Sara; Santos, Marlisa; Shuman, Michael L.; Singer, Robert; Sipiora, Phillip (ReFocus: The American Directors Series : RFADS, 2022)
Offers the first collection of critical essays on Wallace Fox, one of Hollywood's first Native American film directorsExamines the entirety of Fox's career in film and televisionProvides focus on Fox's major works in the areas of the horror film, the western, the women's picture, and the movie serialAnalyses the importance of Fox's role as one of the first Native American directors working in HollywoodBorn in Oklahoma into the Chickasaw Nation, Wallace Fox directed films over the span of four decades. Known primarily for Westerns and mystery films, his output starred such famed actors as Bela Lugosi, Bob Steele, and Lon Chaney. ReFocus: The Films of Wallace Fox includes analysis of some of his best known films, including Wild Beauty, Gun Town, The Corpse Vanishes, Bowery at Midnight, Career Girl and Brenda Starr, Reporter. It reclaims the history and artistry of this major talent